The Influence of Product Attributes and Brand Trust on Purchase Decisions for the Originote Skincare in Surabaya City - Saniyatul Nadhiro; Siti Aminah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Advances in various fields have increased human needs, not only in basic aspects but also in personal needs such as skin care. This study aims to determine the influence of Product Attributes and Brand Trust on the purchase decision of The Originote skincare in the city of Surabaya. This study uses a quantitative approach with primary and secondary data, and the data collection instrument is compiled using a questionnaire with an ordinal scale with the Likert 1-5 technique. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS) through the SmartPLS application. The sampling technique used was purposive sampling, with a total of 110 respondents. The results showed that Product Attributes and Brand Trust had a positive and significant effect on purchase decisions. These findings indicate that the better the consumer's perception of Product Attributes and Brand Trust, the higher their tendency to purchase The Originote skincare products.